High prevalence of severe vitamin D deficiency during the first trimester in pregnant women in Switzerland and its potential contributions to adverse outcomes in the pregnancy (Swiss Medical Weekly, 2020)
PURPOSEVitamin D is primarily known for its role in bone health. However, it has a much more diverse role in the human metabolism. Specifically, deficiency of vitamin D has recently been studied for its possible role in adverse pregnancy outcomes such as preeclampsia, gestational diabetes and preterm birth. Vitamin D levels largely depend on exposure to the sun and are influenced by nutritional habits at only a minimal level. In Switzerland, it is estimated that 40–50% of the population is vitamin D deficient. No specific data on pregnant women is available. The recommendations of the Swiss Federal Commission for Nutrition include a supplement of 600 IU of vitamin D to all pregnant women, despite the lack of data for this population in Switzerland. The primary aim of this study was to determine the prevalence of vitamin D deficiency among the population of pregnant women receiving prenatal care and giving birth at our clinic. We assumed that the prevalence of vitamin D deficiency in pregnant women in Switzerland is significantly higher than what has been estimated. Therefore, the current recommendations for vitamin D supplementation in pregnant women may be insufficient to achieve appropriate vitamin D levels. Furthermore, we aimed to address the issue of the potential influence of vitamin D deficiency on adverse pregnancy outcomes.METHODSWe performed a retrospective, observational cross-sectional study of 1382 pregnant women attending prenatal care at our department between 2012 and 2015. Serum 25-dihydroxycholecalciferol (25(OH)D) levels were determined in the first trimester, and the patient’s characteristics, the course of the pregnancy, any complications, the delivery and the neonatal outcome were analysed. The risk factors for vitamin D deficiency and its correlation with adverse pregnancy outcomes were assessed using a multivariate analysis.RESULTSThe clear majority (73.23%) of the population studied were found to be vitamin D deficient, with serum levels of 25(OH)D